Pengaruh Aktivator Dalam Kompos Takakura Terhadap Tanaman Cabai - Farumi, Shofiyah Salma (Preventia: The Indonesian Journal of Public Health, 2020)
As the population grows, the number of activities increases and the amount of waste in Indonesia increases. Composting is one of the way to reduce waste in Indonesia. Composting is the process of breaking down organic matter with the help of microorganisms.The general time for composting is 3-4 months. To speed it up, activators can be used such as molasse, EM4, and leachate. The aim of the study to determine the effect of molasses, EM4, and leachate in Takakura compost on the height and number of leaves in chili plants. This research is an experimental research. The composting process is 37 days and monitoring the plants for 11 days. The analysis that used are descriptively and statistically. The results of this study indicate the influence of mollases and EM4 activators on the number of leaves of chili plants. The results also showed no effect of all activators (molasses, EM4, and leachate on the height and number of leaves of chili plants).